A 150‐mile ultra‐endurance type 1 diabetes cycling event: qualitative analysis of knowledge, preparation and management strategies. (5th April 2022) - King, Andy J; Pickering, Katie; Pringle, Andy; Kime, Nicky
Abstract: Purpose: The purpose of this study is to characterise the decision‐making and self‐management strategies of individuals with type 1 diabetes (T1D) participating in a 150‐mile ultra‐endurance cycling event and inform health care professionals working in T1D. Participation in ultra‐endurance exercise is becoming increasingly popular in the T1D community and self‐management in this context needs further investigation. Method: Qualitative, semi‐structured interviews were conducted with 12 participants with T1D who took part in the 'Coast to Coast in a Day' cycling sportive. Event‐specific and T1D self‐management strategies in the context of endurance exercise were assessed using the Thematic Network Approach to analysis. Results: Participants reported that they took part in the event 'as a cyclist rather than a type 1 diabetic'. A range of self‐management strategies to manage glycaemic control were identified, but all were grounded in experience of a 'trial‐and‐error' approach to determine 'successful practice'. Engagement with health care professionals in preparation for the event was limited due to a perceived lack of endurance exercise knowledge. Participants reflected that T1D can be controlled in ultra‐endurance events through careful and practised self‐management of energy intake and insulin strategies. Conclusions: Individuals with T1D are capable of taking part and excelling in ultra‐endurance events, but current health care professional advice does not match patient ambition and practice, which is grounded in an identity that is first and foremost as a 'cyclist and person'. Limitations in participants' 'trial‐and‐error' practices require further understanding from health care professionals to provide advice around existing knowledge, preparation and self‐management strategies for ultra‐endurance exercise. Copyright © 2022 John Wiley & Sons.